PENGARUH ORGANIZATIONAL LIFE CYCLE TERHADAP FINANCIAL PERFORMANCE MELALUI INTELLECTUAL CAPITAL SEBAGAI VARIABLE INTERVENING PADA PERUSAHAAN TERBUKA (Tbk) DI SURABAYA - Jansen Jansen; Sarce Elsye Hatane (Business Accounting Review, 2016)
The Affect of Organizational Life Cycle towards Financial Performance through Intellectual Capital as Intervening Variable on manufacturing companies in Surabaya.The purpose of this study was to test the effects of Organizational Life Cycle, towards Financial Performance through Intellectual Capital as Intervening Variable in manufacturing companies in Surabaya. The sample of this study was 30 public companies in Surabaya. The data was collected by distributing questionnaires to the companies. This study used path modeling analysis technique with PLS tools. The results from this study showed that Organizational Life Cycle and Intellectual Capital had negative affect through Financial Performance as the companies growing older.